Rich Merzoug and Afilou N’Khou Veins of the Oumjrane Deposit (Example of Oriental Anti-Atlas Copper Mineralization) - Amina, Wafik; Hicham, Fettah; Lahcen, Rakhiss; Abdelmalek, Ouadjou (European Scientific Journal, ESJ, 2017)
The geological study of the Oumjrane region (Anti-Atlas oriental), carried out within the Oumjrane mining company (CMO), with a view to a detailed study of the two copper strands Rich Merzoug and Afilou N’Khou , So a mapping of ground was made preferably for localization of the different facies and geological structures, with sampling of our magmatic rocks, following a microscopic study. These are dolerite, gabbro to olivine, basalt, the latter are located respectively south of the three exploited veins, Bounhass vein, Afilou N’Khou vein, and Rich Merzoug’s veins. A detailed study of the latter two veins in the second Bani Ordovician quartzite sandstone series will lead to the identification of four hydrothermal stages responsible for the emplacement of the mineralization: stage 1 to calcite siderite, stage 2 Pyrite arsenopyrite, stage 3 galena barite, and stage 4 with chalcopyrite, are followed by supergene stage due to the alteration of copper sulphides. The Oumejerane ore deposits shows lateral zonation from SW (Cu) to NE (Cu-Pb-Ba) and (Cu-Ba), wich underligne temperature decresing from SW to NE.